Improving consumer trust in digital health: A mixed methods study involving people living with chronic kidney disease - Soraia de Camargo Catapan; Monica L Taylor; Paul Scuffham; Anthony C Smith; Jaimon T Kelly (Digital Health, 2025)
Aim To explore preferences, experience and trust in digital health in people living with chronic kidney disease (CKD), and tailor these findings towards solutions that may enhance uptake of digital health services. Methods Mixed methods study, with cross-sectional survey and individual interviews with adults living with CKD attending specialist appointments at an Australian metropolitan hospital. Descriptive statistics and Wilcoxon matched-pairs test were used for survey responses and thematic analysis of interview transcripts, both reported on a theme-by-theme basis provided an overall understanding of trust in digital healthcare. Results Digital health is changing the way health services are provided, and our results demonstrate that despite limited familiarity, participants are open to learn and adapt to existing digital models of care. Limited exposure to technology may undermine trust in digital health, and telehealth can promote improvements in health literacy. Having the choice in healthcare modalities can promote trust, which can arise from trustful relationships with clinicians who demonstrate genuine interest in patient care. Participants expressed more concerns about sharing identity data than health data online and worry about fragmented information among providers. They preferred public health services due to distrust generated by the perceived risk of private sector data commercialisation. Building trust requires increasing awareness of digital health benefits, promoting positive experiences, improving digital literacy and ensuring interoperability and transparency in digital healthcare systems. Conclusion People with CKD want to learn and benefit from digital health. Choice and open disclosure on data management and purpose are paramount to building trust.